(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides scientific information about the concepts of professionogram and professionalism in introducing students to the basics of craftsmanship. Information is also provided about the types of professiograms, their definition and characteristics, the concept of professionalism, what is necessary to pay attention to in the craft.